Faith seeking action : mission, social movements, and the church in motion - Leffel, Gregory P., 1953- (Lanham, Md. : Scarecrow Press : Center for the Study of World Christian Revitalization Movements, 2007)
"The book examines the church as it actualizes its life through its mission to the world and reflects upon this action from a point of view grounded in the wider academic study of social movements."--Provided by publisher.
Mission and movements -- Toward a missio-ecclesiology -- Social movements : an interpretive framework -- The antiglobalization movement -- The sanctuary movement -- The Xenos Christian Gellowship House church movement -- Social movements : an action framework -- Missio-ecclesiology : faith seeking action -- Mission and imagination.
Includes bibliographical references (p. [257]-279) and index.
Keywords: Mission of the church; Missions; Sociology, Biblical; Church and social problems; Social movements -- Religious aspects